Bradycardia in a patient with severe COVID-19 - Zoubi, Magdi; Sheinin, Rivka; Amital, Howard; Mahroum, Naim (NLM (Medline), 2022)
BACKGROUND: Heart rate disorders and in particular sinus arrhythmias are known to accompany viral infections. Sinus tachycardia is prevalent in the presence of increased body temperature and respiratory rate. However, bradycardia has also been described for centuries to complicate viral illnesses.
Keywords: Bradycardia; COVID-19; SARS-CoV-2